Avaliação geoambiental da bacia hidrográfica do Córrego Bagagem, Goiás - GO - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The watersheds are ideal units for the application of geoenvironmental studies and analyzes that aim to measure the consequences of anthropogenic interventions in these systems. In this sense, geoprocessing techniques have contributed to these studies, enabling integrated analyzes of the landscape where it is possible to consider biotic, abiotic and anthropogenic aspects. Thus, this dissertation aimed to develop an integrated geoenvironmental analysis of the landscape in the Watershed of the Bagagem Stream, considering physical and climatic parameters associated with the multiple uses of the soil and water resources. The Bagagem Watershed is located in the municipality of Goiás, state of Goiás, and has an area of 98.7 km². In order to achieve the proposed objective, the pedological, geomorphometric, climatic and land use and land cover characteristics were surveyed and evaluated with applications of geoprocessing techniques. The results and analyzes indicated that the measure of tropical rains that occur in the region increases the occurrence of erosive processes and has a low to median tendency to flooding. The criticality of water deficiency in the soil occurs in the months of August and September, when there is a deficit of 164.9 mm and 157.2 mm, respectively. The Watershed has a very high river density and this is related to structural factors of the relief. The maintenance coefficient is high, requiring an area of 613.5 m² to keep one meter of river channel active. The average runoff length of the Watershed is low, which can cause flooding in days of intense rain, due to the lower capacity of water infiltration in the soil in non-vegetated areas, increasing erosion processes. The biggest slopes in the Watershed are close to the water divisions and are associated with folded and highly dissected reliefs. The main channel has a high slope with potential for river erosion and about 35% of the Watershed area has a high potential for erosion in relation to the profile and flat curvature. The texture of the soils indicated moderate to high erodibility. Cerrado coverages are predominant and occupy a total of 59.14% of the área. The predominant use is for pastures, which have advanced stages of degradation, and there is conflict of use in APPs (Permanent Preservation Areas), mainly planted pastures and dams in water courses and veredas (swampy plains between hills and rivers). The final product of this research has the purpose of subsidizing the management plans of the Watershed of the Bagagem Stream, focusing on the environmental fragilities, mainly in the conflicts of land and water use.
Keywords: Paisagem; Sistema de informações geográficas (SIGs); Uso do solo; Cerrado; Recursos hídricos; Landscape; Geographic information systems; Cerrado; Use of the land; Water resources; CIENCIAS HUMANAS::GEOGRAFIA